A meta de eliminação da hanseníase e a realidade no município de Guarapuava – Paraná - Vieira, Iara Rodrigues (2021)
Introduction: The goal of eliminating leprosy is one of the goals of the World Health Organization (WHO) and the Ministry of Health (MS). For this, the decentralization of the health actions of the Leprosy Control Program (PCH) to the Basic Health Units (UBS) was recommended. Objective: Demonstrate and evaluate the experience of the municipality of Guarapuava/Paraná in the decentralization of health actions from the PCH to the UBS. Method: Observational, descriptive, retrospective and cross-sectional study of data collection from the Notifiable Diseases Information System (SINAN) and records of new cases of leprosy in Guarapuava-PR in the period from 2008 to 2019. Results: In 2001, the municipality of Guarapuava, through an interdisciplinary reference service, decentralized the activities of the Leprosy Control Program to the Basic Health Units and the goal of eliminating leprosy was achieved in 2016, with the incidence of new cases being reduced by more than half. In 2012 there was a record of only one case in a child under 15 years of age. As of 2009, the examination of contacts remained within the good parameter, with no specific treatment being abandoned in any of the years, with a reduction of half of the ulnar neuritis and the total number of fibular neuritis at the end of the treatment. The Degree of Physical Disability 2 (GIF2) showed parameters of medium and high at diagnosis, however at discharge it showed a reduction in incapacities. As for the geospatial distribution of the new cases, a higher incidence was observed in the peripheral neighborhoods. Conclusion: The strategy of using an active interdisciplinary reference service proved to be an important pillar for the decentralization of the PCH to the UBS, with positive results. In this sense, it is suggested to maintain this strategy, together with educational campaigns and collective examination in the area of leprosy, especially in peripheral neighborhoods.